2022
DOI: 10.1093/braincomms/fcac025
|View full text |Cite
|
Sign up to set email alerts
|

p70S6 kinase regulates oligodendrocyte differentiation and is active in remyelinating lesions

Abstract: The p70 ribosomal S6 kinases (S6K1 and S6K2) are downstream targets of the mechanistic target of rapamycin (mTOR) signaling pathway. S6K1 specifically has demonstrated functions in regulating cell size in Drosophila and in insulin-sensitive cell populations in mammals. Prior studies demonstrated that the mechanistic target of rapamycin pathway promotes oligodendrocyte differentiation and developmental myelination; however, how the immediate downstream targets of mTOR regulate these processes has not been eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…We measured phosphorylation of S6RP, a downstream target of mTOR, in brain and spinal cord O4 + cells and found higher levels in spinal cord compared with the brain ( Figure S3F ). A recent report demonstrated that S6RP activation in differentiating oligodendrocytes correlates with the peak of myelination in both brain and spinal cord, but no comparison was made on the relative activation in each region ( Benardais et al, 2022 ). We next asked whether brain and spinal cord oligodendroglia respond differently to the loss of mTOR at the transcriptome level.…”
Section: Resultsmentioning
confidence: 99%
“…We measured phosphorylation of S6RP, a downstream target of mTOR, in brain and spinal cord O4 + cells and found higher levels in spinal cord compared with the brain ( Figure S3F ). A recent report demonstrated that S6RP activation in differentiating oligodendrocytes correlates with the peak of myelination in both brain and spinal cord, but no comparison was made on the relative activation in each region ( Benardais et al, 2022 ). We next asked whether brain and spinal cord oligodendroglia respond differently to the loss of mTOR at the transcriptome level.…”
Section: Resultsmentioning
confidence: 99%
“…β-tubulin was used as a loading control to ensure effective protein transfer and equal sample loading across all wells. For detecting total-S6 ribosomal protein, the same blot was stripped using the Restore™ PLUS Western blot stripping buffer (Thermo Fisher Scientific, Waltham, MA, USA) for ∼8min, washed with 1X tris buffered saline (TBS), blocked for 1 h with 5% BSA, and then probed using the total S6 ribosomal protein [ [66] , [67] , [68] ] rabbit primary antibody (1:1000, 32 kDa). All antibodies were purchased from Cell Signaling Technology (Danvers, MA, USA).…”
Section: Methodsmentioning
confidence: 99%